PROFESIONALISASI GURU PENDIDIKAN AGAMA KATOLIK DI INDONESIA: ANTARA SPIRITUALITAS PANGGILAN DAN PENGAKUAN PROFESIONAL - Luwing, Yosefa; Lorensius, Lorensius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study critically examines the professionalization of Catholic Religious Education (CRE) teachers in Indonesia, revealing an epistemological tension between pedagogical rationality and faith formation. Using a narrative literature review combined with discourse analysis of the 2025 Self-Study Module: Professional Content for CRE, the findings show the dominance of secular-pedagogical discourse that prioritizes learning design, materials, and assessment, while the dimension of faith-based pedagogy and spiritual vocation remains marginal. The study introduces Faith-Based Pedagogical Content Knowledge (FBPCK) as a holistic framework integrating pedagogical competence, spiritual depth, and pastoral identity. It recommends reforming certification modules to include reflective, spiritual, and pastoral formation through guided reflection, spiritual accompaniment, and practice-based portfolios grounded in faith-based professionalism.